Information system programmes: academic myopia?. (13th March 2006) - Shah, Vivek; Martin, Roy; Mehta, Mayur
Information Systems (IS) academic programmes must respond to continuous changes in Information Technology (IT), outsourcing of IT jobs and declining enrolment. This paper examines the future role of IS academic programmes and the consequences if these programmes fail to meet the needs of a dynamic environment.